2000
DOI: 10.1105/tpc.12.5.691
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Silencing of a Plant Cellulose Synthase Gene

Abstract: Specific cDNA fragments corresponding to putative cellulose synthase genes ( CesA ) were inserted into potato virus X vectors for functional analysis in Nicotiana benthamiana by using virus-induced gene silencing. Plants infected with one group of cDNAs had much shorter internode lengths, small leaves, and a "dwarf" phenotype. Consistent with a loss of cell wall cellulose, abnormally large and in many cases spherical cells ballooned from the undersurfaces of leaves, particularly in regions adjacent to vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(114 citation statements)
references
References 46 publications
4
107
0
3
Order By: Relevance
“…2a). Given the difficulties with the methylation of crystalline cellulose (Burton et al 2000), we used the acetic acid-nitric acid values in our final analyses. The differences between the values at one and 2 days were much greater than the differences in older coleoptiles (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2a). Given the difficulties with the methylation of crystalline cellulose (Burton et al 2000), we used the acetic acid-nitric acid values in our final analyses. The differences between the values at one and 2 days were much greater than the differences in older coleoptiles (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Partially methylated alditol acetate and acetic acidnitric acid data were combined to estimate the polysaccharide composition of the walls, based upon the structures of well-characterized wall polysaccharides from Nicotiana plumbaginafolia (Sims and Bacic 1995) and from information in Carpita and Gibeaut (1993), as described previously (Burton et al 2000) and modified here. Uronic acids were estimated from the NaBD 4 -reduced cell wall material.…”
Section: Linkage Analysismentioning
confidence: 99%
“…The cellulosic component of walls is synthesised by products of the CesA genes (Pear et al 1996;Burton et al 2000), and possibly by members of certain Csl genes (Doblin et al 2002). Plant CesA genes are members of multi-gene families, with at least 10 CesA genes in Arabidopsis, 12 in rice, about 12 in maize, and at least 8 in barley (Hazen et al 2002;Doblin et al 2002;Burton et al 2004).…”
Section: The Cesa and Csl Gene Familiesmentioning
confidence: 99%
“…Thus, computer -based database searches enabled them to tentatively identify a cellulose synthase gene ( CesA ) from cotton, for which the encoded protein was classifi ed in the GT2 family of glycosyl transferases (( http://afmb.cnrsmrs.fr/CAZY/ ). Since then, mutational genetics, gene silencing and herbicide studies have provided strong evidence that the catalytic subunits of cellulose synthase enzymes in the rosettes are encoded by CesA genes (Pear et al 1996 ;Arioli et al 1998 ;Burton et al 2000 ;Scheible et al 2001 ;Burton et al 2004 ). Genome sequencing programs and bioinformatical analyses of large EST databases have shown that plant CesA genes are members of multigene families.…”
Section: Cellulose S Ynthesis By E Mbryophytesmentioning
confidence: 99%